CURRENT VOLTAGE CHARACTERISTIC OF PLANAR LANGMUIR PROBE IN IONOSPHERIC MAXWELLIAN PLASMA - Bhattarai, Shankar; Mishra, Lekha Nath (International Journal of Research -GRANTHAALAYAH, 2017)
Frequently used geometries of Langmuir probes are planar, spherical, and cylindrical shapes. The geometry is chosen depending on the purpose of the measurements and the platform configuration. Planar Langmuir Probes have been installed on satellites and sounding rockets to observe the general characteristics of thermal plasma in the ionosphere for more than five decades. Because of its simplicity and convenience, the Langmuir probe is one of the most frequently installed scientific instruments on spacecraft. The Planar Langmuir Probe is the key plasma diagnostic used by scientists interested in plasma characterization to measure the internal parameters of the bulk of the plasma. This research explores the theoretical study of Planar Langmuir Probe I-V Characteristics. The relationship between first derivative of current verses applied probe voltage is also computed. With the help of the (volt–ampere curves) of Planar Langmuir probes, the different parameters of plasma can be determined such as plasma potential, floating potential, probe currents in different probe voltage and so on. Planar Langmuir probe geometry is easy to construct and equally suitable for plasma characterization.